Two Kinds of Entangled Coherent States and Their Nonclassical Effects (Journal of Atomic and Molecular Sciences, 2021)
As for two kinds of entangled coherent states, we have studied the relationship between the entanglement and the nonclassical effects; we calculate their entanglement by the concurrence and their nonclassical effects, such as squeezing and antiquating. We find that the entanglement always corresponds with one of squeezing and antiquating and the larger a nonclassical effect is, the stronger entanglement is. The result shows the entanglement has a deep relationship with the nonclassical effects.
Keywords: entangled coherent states; nonclassical effects; concurrence.